Protective effect of Specnuezhenide on islet Î² cell of rats with gestational diabetes mellitus - Yang, Jing; Jia, Jian; Yang, Yongkang; Zhao, Yaning; Li, Qin (Cellular and Molecular Biology, 2020)
Gestational diabetes mellitus (GDM) refers to diabetes mellitus and impaired glucose tolerance first diagnosed during pregnancy without previous history of the disease. Usually, GDM has a high risk of inducing type 2 diabetes mellitus. The incidence of GDM is increasing year by year worldwide, and it seriously affects the quality of life of patients, and increases the risk to pregnancy. Specnuezhenide (SPZ) is a characteristic active component of Ligustrum lucidum, a plant which exerts a variety of pharmacological effects. In this study, the protective effect of SPZ on Î² cells in gestational diabetes mellitus rats was investigated in a rat model of gestational diabetes. Based on oral glucose tolerance test, ELISA, qRT-PCR and western blotting assays, It was found that SPZ effectively improved blood sugar control and glucose tolerance in gestational diabetic rats, inhibited inflammation in islet tissue, and reduced inflammation-mediated insulin resistance.